1992
DOI: 10.1021/tx00030a008
|View full text |Cite
|
Sign up to set email alerts
|

Fluoranthene metabolism: human and rat liver microsomes display different stereoselective formation of the trans-2,3-dihydrodiol

Abstract: The metabolism of the environmental carcinogen fluoroanthene by human liver microsomes was compared to that by liver microsomes from rats treated with Aroclor 1254. Although the human-derived system gave primarily one product, similar metabolites were noted from each system. Enantiomers of the major metabolic product, in both cases the trans-2,3-dihydrodiol, were separated by chiral stationary-phase chromatography. Absolute configurations were assigned by application of the benzoate exciton chirality rules to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Biotransformation studies of FLA using microsomal preparations from rodent liver tissues revealed that 1-, 3-and 8-hydroxyfluoranthenes, 2,3-dihydro-2,3-dihydroxy FLA and FLA 2,3-dione were the predominant metabolites [28,[41][42][43]. FLA 2,3-diol, one of the predominant metabolites found in our study, has been reported to constitute 29-43% and 70-95% of the total metabolite concentrations in the rat [28] and human [44] hepatic microsomes, respectively. Hydroxyfluoranthenes are not mutagenic in their normal form but may be oxidized to their potentially mutagenic diol counterparts.…”
Section: Discussionmentioning
confidence: 51%
“…Biotransformation studies of FLA using microsomal preparations from rodent liver tissues revealed that 1-, 3-and 8-hydroxyfluoranthenes, 2,3-dihydro-2,3-dihydroxy FLA and FLA 2,3-dione were the predominant metabolites [28,[41][42][43]. FLA 2,3-diol, one of the predominant metabolites found in our study, has been reported to constitute 29-43% and 70-95% of the total metabolite concentrations in the rat [28] and human [44] hepatic microsomes, respectively. Hydroxyfluoranthenes are not mutagenic in their normal form but may be oxidized to their potentially mutagenic diol counterparts.…”
Section: Discussionmentioning
confidence: 51%
“…It has been shown, however, that fluoranthene is metabolized to the corresponding DEs by human liver microsomes (Day et al 1992).…”
Section: Benzo[a]pyrene (Bp) (+)-Bp-78-epoxide (-)-Bp-78-dihydrodiomentioning
confidence: 99%
“…The FADE was synthesized from > 99.9% pure ira«j-2,3-dihydroxy-2,3-dihydrofluoranthene (Day et al, 1992) by epoxidation with 3-chloroperbenzoic acid in CHCI3 and purified by medium-pressure chromatography (dry N2) over DEAE cellulose (Rastetter et al, 1982;Day et al, 1992) MS (miz, % base): 253 (100, [M+H]+). The CPPE was synthesized from 2 mg of CPP (NCI Chemical Carcinogen Repository) that was previously purified to >99% by several flash Si02 Chromatographie runs (petroleum ether).…”
Section: Pah Epoxides and Diol Epoxidesmentioning
confidence: 99%